2020
DOI: 10.2147/idr.s254479
|View full text |Cite
|
Sign up to set email alerts
|

<p>High Prevalence of 16S rRNA Methyltransferase Genes in Carbapenem-Resistant <em>Klebsiella pneumoniae</em> Clinical Isolates Associated with Bloodstream Infections in 11 Chinese Teaching Hospitals</p>

Abstract: Objective: The 16S rRNA methylase-mediated high-level resistance to aminoglycosides has become a great concern. The purpose of the study was to investigate the occurrence of 16S rRNA methyltransferase (RMTase) genes in carbapenem-resistant Klebsiella pneumoniae (CRKP) clinical isolates associated with bloodstream infections (BSIs) in China. Methods: From July 2015 to December 2018, a total of 137 unique CRKP clinical isolates associated with BSIs were collected from 11 Chinese teaching hospitals. PCR and DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…Here, we showed that the annual rate of RMTases among carbapenemase-producing Enterobacterales showed an increasing trend, from 7.5%, 10.7%, and 11.2% to 13% from 2017 to 2020. These results are in the range of those described among K. pneumoniae in Greece, but still less than the prevalence of 42.5%, 56.9%, and 93.4% reported in India, the UK, and China, respectively [8,20,39,40].…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Here, we showed that the annual rate of RMTases among carbapenemase-producing Enterobacterales showed an increasing trend, from 7.5%, 10.7%, and 11.2% to 13% from 2017 to 2020. These results are in the range of those described among K. pneumoniae in Greece, but still less than the prevalence of 42.5%, 56.9%, and 93.4% reported in India, the UK, and China, respectively [8,20,39,40].…”
Section: Discussioncontrasting
confidence: 49%
“…Such a frequent association between carbapenemase-producing and RMTase-producing Enterobacterales was already reported in different parts of the world [5][6][7][8][9][10][11][12][13]21,[27][28][29][30][31][32][33][34][35][36][37]. The origin of those isolates being identified in Switzerland could be autochthonous theoretically; nevertheless, clinical information (only partially obtained and therefore not presented in that study) showed that many of them corresponded to imported cases, and particularly from Eastern European countries, from Italy, and from the Indian subcontinent.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…These cysteine residues are located near the activated methyl of cofactor. One of the cysteine residues act as a catalytic nucleophile and other play an important role in methyl transferase mechanism ( Foster et al, 2003 ; Shen et al, 2020 ). The top 10 best confirmations are shown in Table 5 along with their ZINC ID, number of interactions, interacting residues, dock score, and minimized energy.…”
Section: Resultsmentioning
confidence: 99%
“…From July 2015 to December 2018, we collected 137 unique (one isolate per patient) CRKP isolates from patients with bloodstream infections (BSIs) in 11 tertiary China teaching hospitals to explore the prevalence of 16S rRNA methyltransferase genes ( 31 ). K. pneumoniae strain 1632 and 1864 were selected from them, for they are the only two isolates harboring the novel coexistence of armA , rmtB , and bla KPC .…”
Section: Methodsmentioning
confidence: 99%